Revising acute care systems and processes to improve breastfeeding and maternal postnatal health: a pre and post intervention study in one English maternity unit - Bick Debra; Murrells Trevor; Weavers Annette; Rose Val; Wray Julie; Beake Sarah (BMC, 2012)
Abstract Background Most women in the UK give birth in a hospital labour ward, following which they are transferred to a postnatal ward and discharged home within 24 to 48 hours of the birth. Despite policy and guideline recommendations to support planned, effective postnatal care, national surveys of women's views of maternity care have consistently found in-patient postnatal care, including support for breastfeeding, is poorly rated. Methods Using a Continuous Quality Improvement approach, routine antenatal, intrapartum and postnatal care systems and processes were revised to support implementation of evidence based postnatal practice. To identify if implementation of a multi-faceted QI intervention impacted on outcomes, data on breastfeeding initiation and duration, maternal health and women's views of care, were collected in a pre and post intervention longitudinal survey. Primary outcomes included initiation, overall duration and duration of exclusive breastfeeding. Secondary outcomes included maternal morbidity, experiences and satisfaction with care. As most outcomes of interest were measured on a nominal scale, these were compared pre and post intervention using logistic regression. Results Data were obtained on 741/1160 (64%) women at 10 days post-birth and 616 (54%) at 3 months post-birth pre-intervention, and 725/1153 (63%) and 575 (50%) respectively post-intervention. Post intervention there were statistically significant differences in the initiation (p = 0.050), duration of any breastfeeding (p = 0.020) and duration of exclusive breastfeeding to 10 days (p = 0.038) and duration of any breastfeeding to three months (p = 0.016). Post intervention, women were less likely to report physical morbidity within the first 10 days of birth, and were more positive about their in-patient care. Conclusions It is possible to improve outcomes of routine in-patient care within current resources through continuous quality improvement.